HUKUM WAKAF TANAH DAN PENSERTIFIKATANNYA DI INDONESIA - Mas'ut, Mas'ut (Diponegoro Private Law Review, 2017)
Waqf is a legal act of wakif to separate and / or surrender some of his property to be used permanently or for a certain period of time in accordance with its importance for the purpose of worship and / or general welfare according to sharia. While in the Islamic Law Compilation of waqf is the act of a person or group of persons or law that separates part of his or her belongings and institutes them for the purpose of worship or other common purposes in accordance with the teachings of Islam.The wakaf land application process is made after wakif wakaf pledge wakaf to nadzir waqf before the Authorization Pledge of the Wakaf Pledge (PPAIW). Upon PPAIW to make a Wakaf Pledge Act, PPAIW on behalf of nadzir filed an application at the Local Authority Office of the District / City by enclosing some of the requirements; the certificate of land concerned, the Wakaf Pledge Deed, and the letter of confirmation from the KUA of the local subdistrict on the relevant nadzir. Keywords : wakaf, nadzir, waqf land certificate, deed of pledge of waqf.